Ultra‐high‐density mapping to guide effective His‐bundle pacing. Issue 8 (21st August 2021) - Covino, Gregorio; Magliano, Paolo Liberato; Colimodio, Filomena; Auricchio, Claudia; Provvisiero, Ciro; Volpicelli, Mario
Abstract: Permanent His bundle pacing is a physiological alternative to right ventricular pacing, resulting in a lower probability of pacing‐induced cardiomyopathy and left ventricular ejection fraction deterioration. The combined use of UHD mapping systems allows precise and detailed information on the His bundle location, possibly providing more pacing option locations. Abstract : Permanent His bundle pacing is a physiological alternative to right ventricular pacing, resulting in a lower probability of pacing‐induced cardiomyopathy and left ventricular ejection fraction deterioration. The combined use of UHD mapping systems allows precise and detailed information on the His bundle location, possibly providing more pacing option locations.